The Problem with Wesley's Postmillennialism: An Exegetical Case for Historic Premillennialism in 21st Century Wesleyan Theology and Missions - Christian, Timothy J (The Asbury journal, 2018)
This article presents an exegesis of Revelation 20:1-10 followed by a critical assessment of Wesley’s interpretation of Revelation 20:1-10. Overall, Wesley’s postmillennial interpretation of Revelation 20:1-10 is not supported by an exegetical reading of Revelation 20:1-10 (Scripture); it is not rooted in the early church (tradition); and it is based largely upon the optimism of the 18th century which was shattered by the 20th century (experience). Historic premillennialism, however, does exegetical justice to Revelation 20:1-10 (Scripture), takes seriously the early church’s view (tradition), and accords with our reason and experience in the 21st century (reason and experience). As such, Wesleyans should abandon postmillennialism and instead embrace historic premillennialism for the sake of having a biblically based theology and approach to missions and evangelism in the 21st century.